Educational platforms and tools and their application teaching in a virtual class - Reyes Rodríguez, Rosa María; Duarte Contreras, Edwin Alfredo (2024)
The Internet and the virtual learning environments have diversified the opportunities for teachers by varying and broadening the alternatives for learning and teaching of languages. The new paradigm employs now tools and applications, other than classroom and course books in the learning of foreign languages. The virtual modality has strengthened since COVID appeared worldwide. This course will activate educators using a variety of support media. The purpose of this report is to know how the specialization of the administration of virtual environments for teaching and learning foreign languages was developed during six month and to review the activities carried out during the specialization. The present report will explain the tools that were used during the specialization such as: Canva, Padlet, Nearpod, Kahoot, Flippity, Flipgrid, Powtoon, Liveworksheets and Edpuzzle and also some Educational platforms such as Moodle, Classroom, Google Site, and Edmodo. In addition, the report contains the activities made during the course and a brief explanation about the tools used to create the didactical material.